Analisis PJ. Kepala Daerah yang Memutasi Pegawai Negeri Sipil Tidak Berdasarkan Peraturan Pemerintah Nomor 12 Tahun 2002 Tentang Kenaikan Pangkat PNS dalam Jabatan Struktural dan Peraturan Pemerintah Nomor 53 Tahun 2010 Tentang Disiplin PNS di Lampung - Yuli Ernitasari (PRANATA HUKUM, 2015)
Alleged violations of procedure by a five-acting mutations Regional Head (Pj. Kada) in Lampung. In its recommendation, the fifth mutation KASN decided to cancel the area. These areas are the city of Bandar Lampung, Metro City, South Lampung, East Lampung District, and District Right Way. Recommendations KASN namely Pj. Kada must return the official who appointed the post of promotion. Similarly, relieved officials assigned (Nonjob) must be returned to its original position. The formulation of the problem What should be the procedure of mutated PNS appropriate Government Regulation No. 12 Year 2002 concerning Amendment to the Government Regulation No.99 Year 2000 of promotion of civil servants in structural positions and Government Regulation No. 53 of 2010 on Discipline PNS. Results of the analysis that I get is as follows, That the ordinance mutated PNS in Environmental Lampung Province has not been in accordance with Government Regulation No. 12 Year 2002 concerning Amendment to Government Regulation No. 99 of 2000 of promotion of civil servants in structural positions and Government Regulation No. 53 of 2010 on PNS discipline. Pj. Regional Head should not be arbitrarily mutated, appoint and dismiss civil servants who have positions on the basis of personal interest only. Moreover, civil servants in these positions have a good performance over the years. It's not just a civil servant pro at Pj. That or not.